Graphite carbon nitride/ZnIn2S4 heterojunction photocatalyst with enhanced photocatalytic performance for degradation of tetracycline under visible light irradiation. (November 2017) - Guo, Feng; Cai, Yi; Guan, Weisheng; Huang, Hui; Liu, Yang
Abstract: It is a widespread concern to address the antibiotics in water with low-cost and eco-friendly photocatalysts that could efficiently harvest solar light. Herein, we designed an efficient photocatalyst by integrating the lamellar g-C3 N4 into Znln2 S4 microflowers through a one-step hydrothermal method. The as-synthesized g-C3 N4 /Znln2 S4 heterojunction photocatalysts exhibited evidently enhancement on the photocatalytic activities for the degradation of tetracycline (100 mL, 20 mg/L) compared with pristine g-C3 N4 and Znln2 S4 . Significantly, g-C3 N4 /Znln2 S4 composite with loading 50 wt.% g-C3 N4 showed the highest photocatalytic performance (almost 100% degradation within 120 min), which was around 40 and 22.8 times higher than that of g-C3 N4 and Znln2 S4, respectively. This enhanced photocatalytic activity of g-C3 N4 /Znln2 S4 is mainly attributed to the formation of heterostructure that can efficiently promote the transfer of photoinduced electrons and holes between g-C3 N4 and ZnIn2 S4, restricting the recombination of electron-hole pairs. In addition, a possible mechanism was also proposed. Highlights: g-C3 N4 /ZnIn2 S4 samples were prepared by a one-step hydrothermal method for the sake of degrading TC. g-C3 N4 /ZnIn2 S4 samples were characterized by various characterization technologies. g-C3 N4 /ZnIn2 S4 samples showed outstanding photocatalytic activity compared with the pure g-C3 N4 and ZnIn2 S4.